Functional Reengineering as a Way to Operate Change - Lahmar, Selma; Dehane, Mohammed (Finance and Business Economies Review, 2022)
The presente study ambitions to highlight the importance of functional reengineering as a means to apply a change within the organisation as well as its procedures and its requirements. Throughout this study, we have noticed that functional reengineering turns out to be a recognized necessity in organisations, which need to have an improvement and human development strategy, in front of the technological and economical mutation in the world of business. Reengineering as a radical change helps the organisation face challenges and adapt to its environment. It helps develop and mobilise human skills, alongside the strategy of the organisation while adopting adequate practices. This was confirmed by the applied study at the operational unit - Jijel - affiliated with Algeria Telecom, through which we studied how to apply the process of functional re-engineering in reality and compare it to what is theoretical